2012
DOI: 10.1007/s10646-012-0899-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of three strobilurin fungicide formulations and their active ingredients to tadpoles

Abstract: Fungicide applications in the United States have increased tenfold in the last 5 years. Formulations and active ingredients (AIs) have been demonstrated to cause acute mortality to amphibian life stages. However, there has been little to no discrimination between the toxicity of fungicide formulations and their AIs. Therefore, we compared the acute toxicity of the active ingredients and formulations of the fungicides Headline®, Stratego®, and Quilt® using Bufo cognatus tadpoles exposed to four concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 18 publications
0
29
1
Order By: Relevance
“…Control mortality was less than 5% during toxicity tests, and no adverse effects were observed within treated units until 72 h into the exposure. This is in stark contrast to previous research using H. azteca amphipods and Bufo cognatus tadpoles, in which >80% of observed toxicity occurred within 8 h of exposure [3,29,31]. The LC50 (95% CI) based on time-weighted average pyraclostrobin concentrations was 441 mg/L (359-555 mg/L; Figure 1).…”
Section: Toxicity Studycontrasting
confidence: 79%
See 3 more Smart Citations
“…Control mortality was less than 5% during toxicity tests, and no adverse effects were observed within treated units until 72 h into the exposure. This is in stark contrast to previous research using H. azteca amphipods and Bufo cognatus tadpoles, in which >80% of observed toxicity occurred within 8 h of exposure [3,29,31]. The LC50 (95% CI) based on time-weighted average pyraclostrobin concentrations was 441 mg/L (359-555 mg/L; Figure 1).…”
Section: Toxicity Studycontrasting
confidence: 79%
“…Although this remains unconfirmed for snails, indirect effects on pyraclostrobin toxicity could occur from metconazole and/or the additional formulation adjuvants. Regardless, previous investigations have demonstrated that the additional adjuvants of the commercial formulations did not significantly contribute to toxicity compared with individual strobilurin ingredients [3,31].…”
Section: Toxicity Studymentioning
confidence: 95%
See 2 more Smart Citations
“…The most toxic compound in our study, the top-selling fungicide Headline, is currently applied on 90 different crops from wheat in Canada to soy-beans in Argentina and its use may increase further due to proclamations of increase in crop yield and attractive discounts21. At present, several thousand pesticide products are registered globally and more than 2.3 million tons are applied on a major proportion of the land surface each year22.…”
Section: Discussionmentioning
confidence: 92%